Kompetensi SDM Sebagai Mediasi Dalam Good Governance Dan Anggaran Berbasis Kinerja Pada Pengelolaan Dana BOS - Aviani Widyastuti; Winda Oktamelinia Titong; Ihyaul Ulum (Universitas Muhammadiyah Malang, 2022)
The phenomenon that often occurs in the management of BOS funds is the problem of fraud and ineffectiveness, from 2016 to 2021 there are 240 corruption cases and of these cases the most corruption is related to the use of BOS funds, which is 52 cases. This study aims to examine the effect of Good Governance and Performance-Based Budgeting on BOS Fund Management with HR Competence as an Intervening variable. The sampling method used the census method with the number of respondents 66 people. Questionnaires were distributed to private schools under the Ministry of Religion in Luwuk Regency, Central Sulawesi Province and processed using the Partial Least Square (PLS) method with SmartPLS 3.0. This study uses HR competence which is assessed as one of the factors that can have an indirect influence on the management of BOS funds, and the results of the study show that Good Governance either directly or through HR Competencies has a positive and significant effect on BOS Fund Management, Performance-Based Budgeting has an effect on negative on BOS Fund Management, and Performance-Based Budgeting has no effect on BOS Fund Management through HR Competence.